2009
DOI: 10.1111/j.1466-7657.2009.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' positive attitudes to nutritional management but limited knowledge of nutritional assessment in Korea

Abstract: These findings suggest that nurses have limited nutritional knowledge and they use nutritional assessment criteria poorly in clinical settings. This study provides a framework for developing nutritional management programmes and a standardized protocol for nutritional assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
(23 reference statements)
3
17
0
13
Order By: Relevance
“…This is consistent with the general findings in literature that nurses lack nutritional knowledge that allows them to perform EN competently (Mowe et al, 2008;Kim and Choue, 2009). As mentioned previously, nurses relied on education and internet as sources of knowledge to provide EN care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the general findings in literature that nurses lack nutritional knowledge that allows them to perform EN competently (Mowe et al, 2008;Kim and Choue, 2009). As mentioned previously, nurses relied on education and internet as sources of knowledge to provide EN care.…”
Section: Discussionsupporting
confidence: 92%
“…However, this is not the case according to the literature. For instance, Kim and Choue (2009) reported that nurses had inadequate knowledge of nutritional assessment despite having a positive attitude toward nutritional care of their patients. Similarly, Mowe et al (2008) stated that the Scandinavian doctors and nurses had inadequate nutritional practices because of limited knowledge concerning nutritional assessment, detection of patients at risk for malnutrition, and nutritional management.…”
Section: Introductionmentioning
confidence: 98%
“…The knowledge level in the current study is similar to a previous study in regional Australia about nurses' knowledge of nutrition (60%) (Schaller & James, ); however, the content in the questionnaires from these studies is not comparable. Nurses' nutritional knowledge scores in other countries have been reported to be similar or lower (49−58%) (Park et al ., ; Boaz et al ., ; Yalcin et al ., ); nurses' knowledge about nutritional assessment was reported to be 35% in one study; and knowledge of normal ranges of BMI was 0.9% (Kim & Choue, ), compared with 66% of participants in this study who knew the BMI definitions for overweight and obese.…”
Section: Discussionmentioning
confidence: 97%
“…Many of these studies measured nurses' knowledge about healthy lifestyle and some also reported nurses' practices in the assessment of overweight and obese patients and advice they provided (The Counterweight Project Team, 2004;Miller et al, 2008;Kim & Choue, 2009;Jansink et al, 2010;Martin et al, 2013). Some of these studies measured knowledge, practices or perceptions of health professionals about chronic disease (Jansink et al, 2010;Martin et al, 2013) and only a few were specifically designed to address the problem of people who are overweight or obese (The Counterweight Project Team, 2004;Miller et al, 2008;Park et al, 2011;Aranda & McGreevy, 2014).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation